Evaluation of Some Heavy Metals Levels in Soil and Rice Samples from Some Selected Agricultural Sites in Bauchi State, Nigeria - Aminu Mohammed, Umar; Aliyu Shehu, Aísha; Kolo, Babagana (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
ABSTRACT Heavy metals are persistent metals that bio accumulate in human body through an exposure process and put human health at risk. These metals can be absorbed by crops from the soil used for cultivation, which goes into the human body through consumption of these food products. This study determined the mean concentration of some heavy metals (As, Cd, Cr, Pb, Ni, Zn) in soil and rice cultivated from some selected agricultural sites, Gadau, Giade and Jama’are in Bauchi State using Atomic Absorption Spectrophotometer (AAS). Also Metal Transfer Factor (MTF), Estimated Daily Intake (EDI), Target Hazard Quotient (THQ) and Hazard Index (HI) were calculated to assess the rate of absorption of these metals by rice and health risk associated with consumption of the rice crop. The soil showed a mean concentration order: Zn˃Cr˃Ni˃Pb˃Cd˃As in gadau, Cr˃Zn˃Cd˃Ni˃As˃Pb in giade and Cd˃Zn˃As˃Cr˃Pb˃Ni in Jama’are while rice are in the following order Pb˃Cr˃Zn˃Ni˃As˃Cd, As˃Cr˃Zn˃Cd˃Pb˃Ni, and Cr˃As˃Zn˃Cd˃Pb˃Ni from Gadau site, Giade site and Jama’are site respectively. The determined MTF values were found lower than 1 except Pb, As and Cr in Gadau, Giade and Jama’are sites respectively. This study also shows no health risk associated with consumption of this rice samples because the THQ and HI values were less than 1.